2019
DOI: 10.1088/1361-648x/ab2d6c
|View full text |Cite
|
Sign up to set email alerts
|

Structure and electron affinity of silicon and germanium terminated (0 0 1)-(2 × 1) diamond surface

Abstract: Control over the chemical termination of diamond surfaces has shown great promise in the realization of field-emission applications, the selection of charge states of near-surface colourcentres such as NV, and the realisation of surface-conductive channels for electronic device applications. Experimental investigations of ultra-thin Si and Ge layers yield surface states both within the band-gap and resonant with the underlying diamond valence band. In this report, we report the results of density-functional si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In order to solve the problems of surface oxidation and thermal instability, an effective method is to deposit metal atoms on oxygen (O)-terminated diamond surfaces instead of clean surfaces because the M–O and C–O bonds are stronger and more stable than M–C bonds . Previous results have shown that the adsorption energies and NEA values produced by Sc, Ti, Ni, Cu, and Zn on O-terminated diamond surfaces are greater than those on the clean diamond surfaces. , In addition, other terminations (B, Mg, Al, Si, Ge, and Sn) on diamond surfaces have been reported, which exhibit NEA characteristics. To the best of our knowledge, Zr termination on diamond surfaces has not yet been theoretically investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In order to solve the problems of surface oxidation and thermal instability, an effective method is to deposit metal atoms on oxygen (O)-terminated diamond surfaces instead of clean surfaces because the M–O and C–O bonds are stronger and more stable than M–C bonds . Previous results have shown that the adsorption energies and NEA values produced by Sc, Ti, Ni, Cu, and Zn on O-terminated diamond surfaces are greater than those on the clean diamond surfaces. , In addition, other terminations (B, Mg, Al, Si, Ge, and Sn) on diamond surfaces have been reported, which exhibit NEA characteristics. To the best of our knowledge, Zr termination on diamond surfaces has not yet been theoretically investigated.…”
Section: Introductionmentioning
confidence: 99%